2019
DOI: 10.3390/molecules24030502
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Characterization, Antioxidant and In Vitro Cytotoxic Activity Evaluation of Juniperus oxycedrus Subsp. oxycedrus Needles and Berries

Abstract: In order to evaluate the antioxidant properties of aqueous and methanol extracts of needles and berries of Juniperus oxycedrus subsp. oxycedrus (Joo) species, various antioxidant capacity assessment tests (free radical scavenging assays (DPPH• and ABTS•+ tests), ferrous ions (Fe2+) chelating activity and reducing power assay (FRAP) were conducted. In all of the tests, the extracts exhibited strong antioxidant activity. Furthermore, in-vitro cytotoxic activity assays of the methanolic extracts showed potent cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 42 publications
2
31
0
1
Order By: Relevance
“…Similarly, in our study, the stimulation of activity of the antioxidant enzymes at 400 µg/mL in context with the maximum cytotoxic effect of UBE at the same concentration on CAL 27 cell line could be explained by the production of a large amount of ROS in the tumor cells, which was induced by the dry extract [40]. The increased levels of the antioxidant enzymes activities can be explained as a defense strategy against the oxidative stress induced by UBE.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Similarly, in our study, the stimulation of activity of the antioxidant enzymes at 400 µg/mL in context with the maximum cytotoxic effect of UBE at the same concentration on CAL 27 cell line could be explained by the production of a large amount of ROS in the tumor cells, which was induced by the dry extract [40]. The increased levels of the antioxidant enzymes activities can be explained as a defense strategy against the oxidative stress induced by UBE.…”
Section: Discussionsupporting
confidence: 75%
“…It is known that in the tumor cells exists a higher intrinsic oxidative stress than in the normal cells, due to their metabolic alterations; it was reported that the cancer cells have an important level of ROS, compared to the normal cells. This elevation of ROS may appear as result of an abnormal mitochondrial oxidative metabolism and can be responsible for the initiation and progression of different types of cancer [40]. However, the elevation of ROS to a great level may be lethal for tumor cells themselves [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this work has been conducted at only 4 weeks, another study for the whole cycle of wheat should be conducted to validate this hypothesis. It is known that the glutathione-dependent system requires NADPH, as cofactor, to face reactive oxygen species resulted from the oxidative stress [27]. Therefore, low content of NADPH can disturb the cell response to these toxic compounds.…”
Section: Effect Of Ure On Plant Growth and Oxidative Stress Metabolism Of Wheat Plantsmentioning
confidence: 99%
“…Ethanolic extract of Juniperus turbinate was more potent cytotoxic than cisplatin in human breast adenocarcinoma MDA-MB-231 cell lines [357]. Juniperus oxycedrus ethanolic extract from needles and berries showed potent cytotoxic effects against two breast cancer cell lines (MDA-MB-468 and MCF-7), with no cytotoxicity towards normal cells (PBMCs) [358]. Satureja khuzistanica (Figure 7a (Araliaceae) showed antiproliferative actions on human MCF-7 breast cancer cells [359].…”
Section: Camptotheca Acuminate (Xǐ Shù or Happy Tree) Leavesmentioning
confidence: 99%